Monolithic Si nanocrystal/crystalline Si tandem cells involving Si nanocrystals in SiC. (4th April 2016) - Schnabel, Manuel; Canino, Mariaconcetta; Schillinger, Kai; Löper, Philipp; Summonte, Caterina; Wilshaw, Peter R.; Janz, Stefan
Abstract: Monolithic tandem cells involving a top cell with Si nanocrystals embedded in SiC (Si NC/SiC) and a c‐Si bottom cell have been prepared. Scanning electron microscopy shows that the intended cell architecture is achieved and that it survives the 1100 °C anneal required to form Si NCs. The cells exhibit mean open‐circuit voltages Voc of 900–950 mV, demonstrating tandem cell functionality, with ≤580 mV arising from the c‐Si bottom cell and ≥320 mV arising from the Si NC/SiC top cell. The cells are successfully connected using a SiC/Si tunnelling recombination junction that results in very little voltage loss. The short‐circuit current densities jsc are, at 0.8–0.9 mAcm −2, rather low and found to be limited by current collection in the top cell. However, equivalent circuit simulations demonstrate that in current‐mismatched tandem cells such as the ones studied here, higher jsc, when accompanied by decreased Voc, can arise from shunts or breakdown in the limiting cell rather than improved current collection from the limiting cell. This indicates that Voc is a better optimisation parameter than jsc for tandem cells where the limiting cell exhibits poor junction characteristics. The high‐temperature‐stable cell architecture developed in this work, coupled with simulations highlighting potential pitfalls in tandem cell analysis, provides a suitable route for optimisation of Si NC layers for photovoltaics on a tandem cell device level. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Tandem cells involving a top cell with Si nanocrystals embedded in SiC and a c‐Si bottom cell have been prepared and exhibit open‐circuit voltages Voc exceeding 900 mV, of which over 320 mV arise from the top cell. Short‐circuit current is limited to 0.8‐0.9 mAcm −2 by current collection in the top cell. Equivalent circuit simulations show that shunts in the top cell can provide a path for additional photocurrent collection from the bottom cell but lead to decreased Voc .